Effect of Some Containers, Chemicals and Indigenous Materials on Incidence of Wheat Pests in Storage (Journal of Agriculture & Rural Development, 2010)
The experiment was conducted to evaluate the effect of some containers, chemicals and indigenous materials for protection of wheat seed in storage at the Entomology Laboratory of Sher-e-Bangla Agricultural University (SAU), Dhaka. Wheat seeds were stored in four types of containers (Tin kouta, earthen pot, plastic container and gunny bag) with two types of chemicals (Naphthalene and camphor) and two indigenous materials (neem leaf powder and sand). Among the different containers, the lowest population of grain moth (1.40-7.93), red flour beetle (6.40-35.33) and rice weevil (0.20-9.13) was recorded from the plastic containers. At the initial stage of storage, grain moth was dominant but red flour beetle was abundant at the middle and later stage of storage. Population of rice weevil was gradually increased with storage period. Considering the storage materials, the lowest population of grain moth (3.92-28.98), red flour beetle (7.58-43.08) and rice weevil (0.75-9.08) was found in naphthalene. Camphor had the similar population level of those three insect pests during the study period. Key words: Grain moth; rice weevil; red flour beetle; neem leaf powder; camphor; naphthalene. DOI: 10.3329/jard.v7i1.4429 J Agric Rural Dev 7(1&2), 107-113, June 2009